Pertanggung jawaban pidana terhadap pelaku main hakim sendiri (Eigenrichting) putusan nomor: 194/Pid.B/2022/PN Unaha - Sakti, La Ode Awal; Haerani, Yeni; Yahyanto, Yahyanto; Adam, Ade Caesar Premadani (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Vigilantism (eigenrichting) is the act of punishing another person without going through the applicable legal process. This action can be categorised as a criminal offence, because it is contrary to the provisions of Article 1 of the Criminal Code which states that every person is prohibited from committing acts prohibited by law. The purpose of this study is to determine the concept of the criminal offence of vigilantism (eigenrichting) according to positive criminal law in Indonesia as well as to know and understand the form of criminal liability for the perpetrators of vigilantism (eigenrichting). This research uses normative-empirical legal research methods. The results showed that the concept of vigilantism (eigenrichting) according to positive criminal law in Indonesia that has been applied by the Public Prosecutor at the Konawe District Prosecutor's Office is Article 170 of the Criminal Code on Robbery, Article 338 of the Criminal Code on Murder, and Article 351 of the Criminal Code on Maltreatment. Criminal responsibility for the perpetrators of vigilantism (eigenrichting) in Decision Number: 194/Pid.B/2022/PN, the perpetrators are responsible for their actions based on their position and the form of their actions. The Panel of Judges applied Article 55 Paragraph (1) to 1 of the Criminal Code which regulates the position of the perpetrator in the participation of a criminal offence declared as a pleger (perpetrator) by the Panel of Judges of the Unaha District Court.